CHANGES IN FOOD WASTE LEVEL IN THE EU COUNTRIES - Koszela, Grzegorz; Szczęsny, Wiesław (Acta Scientiarum Polonorum. Oeconomia, 2017)
Food waste is the world-wide social and economic problem, and also large and unnecessary burden for the environment. In this paper was taken the problem of comparing changes in the level of food wastage in the EU countries in 2000–2011. There were used two techniques: multidimensional comparative analysis (MCA) and grade data analysis (GDA). The second one is used for the first time in this type of issues. Based on these techniques there were built synthetic indicators, which were used as a criterion for classification of EU countries in terms of the pace of reducing the level of food waste. It appears that usage of different techniques to construction of indicators gave a divergent arrangements.